2022
DOI: 10.3390/genes13091550
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Complete Chloroplast Genomes of Nine Species of Litsea (Lauraceae): Hypervariable Regions, Positive Selection, and Phylogenetic Relationships

Abstract: Litsea is a group of evergreen trees or shrubs in the laurel family, Lauraceae. Species of the genus are widely used for a wide range of medicinal and industrial aspects. At present, most studies related to the gene resources of Litsea are restricted to morphological analyses or features of individual genomes, and currently available studies of select molecular markers are insufficient. In this study, we assembled and annotated the complete chloroplast genomes of nine species in Litsea, carried out a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
5
8
0
Order By: Relevance
“…In this study, the use of codons in the nucleotide sequence of protein-coding genes of the chloroplast genome of F. simplicissima tends to be specific codons used more frequently than other synonymous codons. This result was consistent with previous related reports [32][33][34][35][36]. The level of use of codons varies between individuals within species and between species of the genus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the use of codons in the nucleotide sequence of protein-coding genes of the chloroplast genome of F. simplicissima tends to be specific codons used more frequently than other synonymous codons. This result was consistent with previous related reports [32][33][34][35][36]. The level of use of codons varies between individuals within species and between species of the genus.…”
Section: Discussionsupporting
confidence: 93%
“…However, most codons with an RSCU > 1 of the chloroplast genome of Litsea contained either an A-or G-terminal. By contrast, RSCU values for codons that ended with a C-terminal, such as CGC (Arg), UGC (Cys), CAC (His), and AGC (Ser), were relatively low [32,34].…”
Section: Discussionmentioning
confidence: 91%
“…The Ka/Ks ratio mainly reflects the selection pressure of protein-coding genes, which is a meaningful way to detect whether protein-coding sequences have evolved. In this study, the vast majority of Ka/Ks ratios were less than 1% (97%), indicating that most of the genes in the Lauraceae family undergo purification selection, which was consistent with the results of previous studies in the Lauraceae family [ 72 ]. Moreover, the results showed that two Ka/Ks ratios were more significant than 1 ( matK , ndhA ), indicating that they were significantly positively selected.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, there are few Ka/ka analyses of Lauraceae. Previous studies found that only two genes, rpl16 and ycf2 , had Ka/Ks values greater than 1 through the analysis of nine Lauraceae species [ 72 ]. Sequence mutational hotspots, also known as hyper-variable regions, provide a reference for designing accurate and efficient molecular markers and species barcodes [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only two genes, the ycf2 gene in P. zhennan and the rpl16 gene in P. tavoyana , were under positive selection. Based on earlier evolutionary assessments of Litsea species ( Song et al, 2022b ) as well as Phoebe species here, the majority of the coding genes in Lauraceae species remained stable during the evolution process, except for ycf2 and rpl16 genes. The comparative analysis revealed that the chloroplast genomes of Phoebe were relatively conserved, which could practically inform future studies on Lauraceae species.…”
Section: Discussionmentioning
confidence: 72%